Resolving the tension between the section 25 Right to Property and section 26 Right to Housing The Constitutional Court of South Africa subsidiarity methodology - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.